Study of Complex Helical Drill with a “S” Type Chisel Edge Tip Orient to Carbon Fiber Reinforced Plastics - Yu He; Xiaolong Zhou; Ping Zou; Kun Liu (Advances in Materials Science and Engineering)
In this paper, a complex helicoids’ drill tip of “S” type chisel edge grinded with a three-parallel universal CNC grinding machine tool is carefully studied to obtain the optimum drill bit tip geometry parameters. The effects of experimental parameters, such as apex angle, chisel edge incline angle, and structure circumference rear angle, on the quality of the drilling hole and the machining force were studied from the orthogonal experiment compared with the ordinary drill bit. The range of technological parameters are confirmed which should be used during the drilling process of carbon fiber reinforced plastics (CFRP) in order to realize the reduction of cutting defects such as cutting force and spurs. The effect of spindle speed and feed on the drilling behaviour of the experiment using optimum complex helicoids’ drill tip is also analyzed. It is found that the feed has a great influence on the drilling axial force and the spindle speed has little influence on axial force, but great influence on torque.